2019
DOI: 10.1128/aac.01403-19
|View full text |Cite
|
Sign up to set email alerts
|

Identification of FosA8, a Plasmid-Encoded Fosfomycin Resistance Determinant from Escherichia coli, and Its Origin in Leclercia adecarboxylata

Abstract: A plasmid-located fosfomycin resistance gene, fosA8, was identified from a CTX-M-15-producing Escherichia coli isolate recovered from urine. Identification of this gene was obtained by whole-genome sequencing. It encoded FosA8, which shares 79% and 78% amino acid identity with the most closely related FosA2 and FosA1 enzymes, respectively. The fosA8 gene was located on a transferable 50-kb plasmid of IncN type encoding high-level resistance to fosfomycin. In silico analysis and cloning experiments identified f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Then, genomic libraries and sequencing were performed using a strategy adapted to the Illumina MiniSeq system as reported previously (9) with 300-bp paired-end reads and a coverage of 50 times. The generated FastQ data were compiled and analyzed using the CLC Genomic Workbench (version 7.5.1; CLC Bio, Aarhus, Denmark), with reads assembled as described previously (9); resulting contigs were uploaded into the Center for Genomic Epidemiology server (http://www .genomicepidemiology.org/). Even though the total assembly process could not close the sequence of the natural plasmid because of repeated sequences, it did confirm that the fosL1 plasmid was indeed the IncX1, with no other plasmid backbone identified from the transconjugant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, genomic libraries and sequencing were performed using a strategy adapted to the Illumina MiniSeq system as reported previously (9) with 300-bp paired-end reads and a coverage of 50 times. The generated FastQ data were compiled and analyzed using the CLC Genomic Workbench (version 7.5.1; CLC Bio, Aarhus, Denmark), with reads assembled as described previously (9); resulting contigs were uploaded into the Center for Genomic Epidemiology server (http://www .genomicepidemiology.org/). Even though the total assembly process could not close the sequence of the natural plasmid because of repeated sequences, it did confirm that the fosL1 plasmid was indeed the IncX1, with no other plasmid backbone identified from the transconjugant.…”
Section: Resultsmentioning
confidence: 99%
“…conferring high resistance to fosfomycin once expressed (3)(4)(5)(6)(7)(8)(9)(10). The natural reservoir of the fosA genes has been identified, as members of the Enterobacteriaceae family such as Enterobacter spp.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13 Until now, nine subtypes of fosA genes have been identified. 10,12,[14][15][16][17] fosA3, the most widespread fosA gene in E. coli, has been detected in human and animal isolates from more than 12 countries, especially in food-producing animal-associated isolates from China. 12,[18][19][20] All fosA subtypes, except fosA2 and fosA7, are identified in plasmids, and they are usually originated from the chromosomal gene of Enterobacteriaceae species.…”
Section: Introductionmentioning
confidence: 99%
“…12,[18][19][20] All fosA subtypes, except fosA2 and fosA7, are identified in plasmids, and they are usually originated from the chromosomal gene of Enterobacteriaceae species. 14,16,17,[21][22][23] In this study, we reported a novel plasmid-encoded fosA variant, fosA10, in an ESBL-producing E. coli isolate, and characterized the genetic context of fosA10 to identify its origin.…”
Section: Introductionmentioning
confidence: 99%